Digitalisasi Pembuktian Elektronik dalam Sengketa Wanprestasi Transaksi Fintech - Desi Syamsiah; Aris Setyo Nugroho; Elvina Eka Damayanti (JOSH: Journal of Sharia, 2026)
The development of financial technology (fintech) as an innovation that integrates technology in financial services has changed the paradigm of economic transactions. Financial Technology (Fintech) is the implementation of information technology utilization in the financial system that produces new products, services, and business models as stipulated in Bank Indonesia Regulation No. 19/12/PBI/2017. Along with the increase in fintech transactions, there has also been an increase in default disputes involving electronic evidence in their resolution. The main challenge that arises is the validity of electronic evidence in the trial of default disputes in fintech transactions. In Indonesia, electronic evidence has a legal basis through Law No. 11 of 2008 jo. Law No. 19 of 2016 concerning Electronic Information and Transactions which recognizes the existence of electronic documents as valid evidence. This writing uses a normative juridical method by analyzing the laws and regulations on electronic transactions and civil procedural law. The results of the writing show that the electronic evidence system still faces technical and juridical obstacles in its application, especially regarding authentication, data security, and standardization in the examination of electronic evidence in court.